Students’ Perceptions of the Benefits of Mobile Polling Technology in Teaching and Learning in College: Implications of Students’ Participation and Academic Performance - Ismail, Ismail; Elihami, Elihami; Mustakim, Mustakim (Jurnal Pendidikan Progresif, 2019)
Students’ perceptions of the benefits of mobile polling technology in teaching and learning in college: Implications of student’ participation and academic performance. Objectives: This study aims to analyze students’ perceptions of interactive teaching using Poll-Everywhere application as a useful teaching methodology. Methods: Strategic Lecturers enter questions using the Poll-Everywhere application. Students’ perceptions of interactive teaching that effectively uses this technology are statisticallyevaluated using a questionnaire. Findings:The level of student academic ability increasedsignificantly between the two sections for Reading III Test (M = 89.74, SD = 3.26), and Reading V (M = 90.42, SD = 3.91). Conclusions: Students consider it a useful method for giving real feedback,which encourages their performance and participation. Lecturers regard Poll-Everywhere as an effectiveteaching innovation that encourages deeper information storage and as an effective teaching aid inmonitoring student progress and identifying shortcomings. Keywords: Poll-Everywhere, student’ participation, academic performance, feedback, Mobile Polling.DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201912